2009
DOI: 10.1364/oe.17.014029
|View full text |Cite
|
Sign up to set email alerts
|

Mapping total suspended matter from geostationary satellites: a feasibility study with SEVIRI in the Southern North Sea

Abstract: Geostationary ocean colour sensors have not yet been launched into space, but are under consideration by a number of space agencies. This study provides a proof of concept for mapping of Total Suspended Matter (TSM) in turbid coastal waters from geostationary platforms with the existing SEVIRI (Spinning Enhanced Visible and InfraRed Imager) meteorological sensor on the METEOSAT Second Generation platform. Data are available in near real time every 15 minutes. SEVIRI lacks sufficient bands for chlorophyll remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 25 publications
1
59
0
Order By: Relevance
“…MODIS sensors have 36 spectral bands with three spatial resolutions of 250 m, 500 m and 1 km, but only 5 bands are used for SPM retrieval: the two SWIR bands at 1240 and 2130 nm with a spatial resolution of 500 m (or NIR bands at 748, 869 nm with a spatial resolution of 1 km, depending of the selected atmospheric correction algorithm (e.g., [36])), the green band at 555 nm with a spatial resolution of 500 m and the red and NIR bands at 645 and 859 nm respectively with a spatial resolution of 250 m. SEVIRI provides data at a high temporal resolution with an image recorded every 15 min. Twelve spectral bands are available but only two can be used for SPM retrieval, the 635 nm spectral band (VIS0.6) used for SPM mapping and the 810 nm spectral band (VIS0.8) used for atmospheric corrections [19]. These spectral bands have a spatial resolution of 3ˆ3 km at the sub-satellite point, but due to the latitude of the study area the pixel are elongated to~3ˆ5 km.…”
Section: Data Specificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…MODIS sensors have 36 spectral bands with three spatial resolutions of 250 m, 500 m and 1 km, but only 5 bands are used for SPM retrieval: the two SWIR bands at 1240 and 2130 nm with a spatial resolution of 500 m (or NIR bands at 748, 869 nm with a spatial resolution of 1 km, depending of the selected atmospheric correction algorithm (e.g., [36])), the green band at 555 nm with a spatial resolution of 500 m and the red and NIR bands at 645 and 859 nm respectively with a spatial resolution of 250 m. SEVIRI provides data at a high temporal resolution with an image recorded every 15 min. Twelve spectral bands are available but only two can be used for SPM retrieval, the 635 nm spectral band (VIS0.6) used for SPM mapping and the 810 nm spectral band (VIS0.8) used for atmospheric corrections [19]. These spectral bands have a spatial resolution of 3ˆ3 km at the sub-satellite point, but due to the latitude of the study area the pixel are elongated to~3ˆ5 km.…”
Section: Data Specificationsmentioning
confidence: 99%
“…SEVIRI L1.5 data were obtained from the EUMETSAT website (eumetsat.int) and cropped to the North Gulf of Lion region (127ˆ36 pixels). The water-leaving reflectance was obtained at the VIS0.6 band after correcting SEVIRI data for (1) atmospheric gas absorption; (2) Rayleigh scattering; (3) scattering by aerosols following the processing detailed in [19,20]. This atmospheric correction algorithm uses an approach similar to the MUMM correction [37] with the red (VIS0.6) and NIR (VIS0.8) bands of SEVIRI (called MUMM-S here after, see details in Table 1).…”
Section: Satellite Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…SEVIRI is capable of imaging the hemisphere of the Earth every 15 minutes at a 3km resolution, while GOCI provides data at 500 m spatial resolution over a 625,000 km 2 area centred on the Korean Peninsula every 1 hour. SEVIRI was not designed primarily for applications over water but several studies have shown the feasibility of retrieving TSM in turbid waters (Neukermans et al, 2009;Neukermans et al, 2012). The GOCI sensor, however, is specifically designed for ocean colour applications and thus can be used to estimate Chl-a concentrations and at a spatial resolution that also allows data to be acquired for systems ranging in scale from shelf-seas to large lakes (Lyu et al, 2015).…”
Section: Special Issue Science Of the Total Environmentmentioning
confidence: 99%